The Influence of Risk and Psychopathy on the Therapeutic Climate in Sex Offender Treatment. (April 2013) - Harkins, Leigh; Beech, Anthony R.; Thornton, David
The current study examines the relationship between therapeutic climate of sexual offender treatment groups, risk level, psychopathy and phase (i.e., early/later) of treatment. The participants were 137 sexual offenders detained indefinitely under Wisconsin's Sexually Violent Person's Law who attended a treatment group based on their level of psychopathy: higher levels of psychopathy (i.e., PCL-R scores of 25 or above) or lower levels of psychopathy (i.e., PCL-R scores of less than 25). Using MANOVA with aspects of the therapeutic climate as the dependent variables, the therapeutic climate did not differ as a function of the risk level of the participants. However, the overall therapeutic climate of the two treatment tracks (Lower vs. Higher PCL-R) differed significantly. The mean therapeutic climate scores for both treatment tracks were in the medium to high range (with exception of group cohesion, which was low in the Higher PCL-R track), indicating a fairly positive therapeutic climate in both treatment tracks overall. The therapeutic climate also differed as a function of phase of treatment for each of the treatment tracks, with some aspects being rated more positively early in treatment and others in more positively in later phases. In particular, group cohesion was viewed more positively for the Higher PCL-R group in later phases of treatment.